Herb induced liver injury after using herbal medicine: A systemic review and case-control study. Issue 13 (March 2019) - Lin, Nai-Hui; Yang, Hsiu-Wu; Su, Yu-Jang; Chang, Chen-Wang
Abstract : Abstract: In Taiwan, traditional herbal medication was included in Taiwan's National Health Insurance (NHI) system since 1996 and in 9 out of 10 hospitals have developed their own departments of traditional medicine. This study aims to address the herb-induced liver injury (HILI) after using herbal medicine on the relationship between age, gender, epidemiology, laboratory data, pathogenesis, mobility, and mortality. We searched the PubMed database with "hepatitis after herbal medicine" and "in human" till 2018 April and returned 163 articles in a systemic review manner. Two cases reports describing in-vitro liver injury were excluded. Reviews and articles without the detailed report, laboratory data and history were excluded from this study. In the end, there were 53 articles enrolled in this study. These enrolled literatures are from France (n = 13), Germany (n = 12), Switzerland (n = 5) United States of America (n = 4), Korea (n = 4), Hong Kong (n = 4), Greece (n = 3), China (n = 2), Canada (n = 1), Italy (n = 1), Thailand (n = 1), Finland (n = 1), Taiwan (n = 1), and Japan (n = 1). The data were analyzed with a commercial statistical software Stata/SE 12.0 program Stata Corporation, College Station, TX, USA. Statistical χ 2 tests were performed and the significance was set at a P value of less than .05 (2-tailed). The ages are ranged from 15 to 78 years with the mean ± SD (standard deviation) of 48.3 ± 16.2 years old. The majority of cases are female (n = 37). In elderly, man is more commonly seen than female in HILI (37.5% vs 10.5%, P  = .02). Female is vulnerable to cholestatic type of HILI than male (21.1% vs 0.0%, P  = .04). Of all the cases in HILI, using pure substance are more commonly seen than mixed substance ( P  = .02). In gender, male patients have higher alanine aminotransferase (GPT) (IU/L) level in HILI than female ones (1560 ± 819 vs 1047 ± 706, P  = .03). In HILI, the female is more commonly seen than male, but less than male in the elderly. The pure substance more often happens to HILI than mixture substance. Female is predominant in the cholestatic type of HILI. The major prevalence of HILI is in Europe rather than Asia. HILI cases in Europe is 2.75-fold than in Asia. This could be due to fewer reports of the herb induced liver injury in Asia compared to Europe. Prevention of HILI is the best policy, because it needs to take 78 ± 59 days to recover.